Step-by-Step Success: Transforming LibGuides and the A-Z Database List in an Academic Library. - Jeffcoat, Heather; Moorthy, Anu; Holdsworth, Liz; Patrick, Martin; Givens, Marlee (Internet Reference Services Quarterly)
This case study examines applying project management principles to overhaul LibGuides and the A–Z database list, improving user experience, organizational efficiency, and accessibility. The project evolved from Library Next successes to tackle outdated content and inconsistent design by creating standardized templates and style guides while enhancing usability through new workflows. Achieving sustainable change requires both cross-departmental collaboration and stakeholder engagement to overcome resistance. The implementation of OpenAthens authentication enables users to securely and consistently access electronic resources. Through a comprehensive phased approach, structured planning with inclusive teamwork and user-centered design led to significant enhancements in library services.